2021
DOI: 10.1371/journal.ppat.1009403
|View full text |Cite
|
Sign up to set email alerts
|

A swine arterivirus deubiquitinase stabilizes two major envelope proteins and promotes production of viral progeny

Abstract: Arteriviruses are enveloped positive-strand RNA viruses that assemble and egress using the host cell’s exocytic pathway. In previous studies, we demonstrated that most arteriviruses use a unique -2 ribosomal frameshifting mechanism to produce a C-terminally modified variant of their nonstructural protein 2 (nsp2). Like full-length nsp2, the N-terminal domain of this frameshift product, nsp2TF, contains a papain-like protease (PLP2) that has deubiquitinating (DUB) activity, in addition to its role in proteolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…At early timepoints, lower nsp2 frameshift efficiency means more ribosomes continue to translate the remainder of pp1a or pp1ab, which encode components of the replication and transcription complex (RTC), which may be more important for establishing infection than translation of the accessory protein nsp2TF. Later in the replication cycle, higher −2 PRF efficiency likely corresponds to an increased requirement for nsp2TF to prevent degradation of GP5 and M, which are expressed from ~8 hpi and are essential for virion assembly 36,123 . Further, nsp2TF is a more potent innate immune suppressor than nsp2, and down-regulates expression of swine leukocyte antigen class I (swine MHC class I) 32,124 , which may become critical later in infection as viral proteins and double-stranded RNA accumulate due to viral translation and replication.…”
Section: Discussionmentioning
confidence: 99%
“…At early timepoints, lower nsp2 frameshift efficiency means more ribosomes continue to translate the remainder of pp1a or pp1ab, which encode components of the replication and transcription complex (RTC), which may be more important for establishing infection than translation of the accessory protein nsp2TF. Later in the replication cycle, higher −2 PRF efficiency likely corresponds to an increased requirement for nsp2TF to prevent degradation of GP5 and M, which are expressed from ~8 hpi and are essential for virion assembly 36,123 . Further, nsp2TF is a more potent innate immune suppressor than nsp2, and down-regulates expression of swine leukocyte antigen class I (swine MHC class I) 32,124 , which may become critical later in infection as viral proteins and double-stranded RNA accumulate due to viral translation and replication.…”
Section: Discussionmentioning
confidence: 99%
“…Programmed −1 frameshifting occurs just 5′ of the junction of its long ORF1a with its long ORF1b to synthesize its replicase polyprotein [ 117 , 118 ]. However, within the nsp coding sequence of ORF1a, PRRSV also employs 20% efficient −2 frameshifting, to generate a multifunctional product, nsp2TF ( T rans- F rame), consisting of the N-terminal of nsp2 and a unique C-terminal domain [ 119 , 120 ]. Immediately 3′ of the shift site, there is a stop codon in the -1 frame.…”
Section: More Recently Identified Viral Recoding Points To Greater Mechanistic Diversitymentioning
confidence: 99%
“…In vitro transfection experiments showed that their deubiquitinase activity suppresses the innate immune response [ 232 , 233 , 234 ]. Nsp2TF has been directly shown to function as a deubiquitinase that antagonizes ubiquitination of host cell proteins [ 120 , 231 ]. However, in infected cells nsp2 localizes to the virus replication complex for polyprotein processing.…”
Section: Immune Evasionmentioning
confidence: 99%
See 2 more Smart Citations